2008
DOI: 10.2337/db08-0425
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Type 2 Diabetes Based on Polymorphisms From Genome-Wide Association Studies

Abstract: OBJECTIVE-Prediction of type 2 diabetes based on genetic testing might improve identification of high-risk subjects. Genome-wide association (GWA) studies identified multiple new genetic variants that associate with type 2 diabetes. The predictive value of genetic testing for prediction of type 2 diabetes in the general population is unclear. RESEARCH DESIGN AND METHODS-We investigated 18polymorphisms from recent GWA studies on type 2 diabetes in the Rotterdam Study, a prospective, population-based study among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
209
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(227 citation statements)
references
References 28 publications
17
209
0
1
Order By: Relevance
“…Combining the GRS with conventional risk factors slightly but significantly improved case-control discrimination for type 2 diabetes risk. Several previous studies have shown that GRS could be used as a simple proxy of an individual's genetic predisposition to type 2 diabetes [2][3][4][5][6]. Consistent with this, we found that each additional risk allele increased the risk of type 2 diabetes by approximately 18% and that participants with a GRS ≥19.0 (8.87%) had a 4.58-fold increased risk of type 2 diabetes compared with those with a GRS ≤11.0 (7.63%).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the GRS with conventional risk factors slightly but significantly improved case-control discrimination for type 2 diabetes risk. Several previous studies have shown that GRS could be used as a simple proxy of an individual's genetic predisposition to type 2 diabetes [2][3][4][5][6]. Consistent with this, we found that each additional risk allele increased the risk of type 2 diabetes by approximately 18% and that participants with a GRS ≥19.0 (8.87%) had a 4.58-fold increased risk of type 2 diabetes compared with those with a GRS ≤11.0 (7.63%).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, gene-environment interaction appears to play an important role, and genetic tests should undergo the same analysis of predictive power as phenotype-based tests. In most cases, a brief look at a patient's body weight as well as a brief family history of disease may tell a doctor much more about his or her risk for diabetes or myocardial infarction than a predictive genetic test (van der Net et al 2009;van Hoek et al 2008;Janssens and van Duijn 2008). Consequently, the additional value of predictive genetic testing may be quite limited, even if the genotype is significantly associated with the risk of the disease outcome.…”
Section: Do the Issues Call For Genetic Exceptionalism?mentioning
confidence: 99%
“…However, the results of these 2 studies, and also a 3rd large study from the Netherlands [24], show that currently available genetic information provides only a negligible improvement in the prediction of T2DM compared to using routinely available clinical information. In addition to T2DM, commercial DNA tests are currently also available for myocardial infarction, atrial fibrillation, glaucoma, prostate cancer and breast cancer.…”
Section: Interaction Effect Of Genetic Polymorphisms In Glucokinase (mentioning
confidence: 99%